Prepared Concrete Made by Recycled Construction Materials - Contreras Vásquez , Luis Felipe (2023)
This study covers the resistance to compression analysis of traditional concrete compared to the resistance parameters of concrete prepared using recycled construction materials such as: concrete from building demolitions, sidewalk debris and curbs; substituting the coarse aggregate in percentages of 25%, 50%, 75% and 100%. With a substitution of 25%, a resistance to compression of 244.97 kg/cm2 was achieved, increasing the substitution percentage by 50%, 75%, and 100%, it showed a decrease in resistance (220 kg/cm2) in comparison to the 25% of substitution. It was concluded that the tests performed, revealed relevant results, allowing us to determine that recycled material from construction waste might be considered for manufacturing new concrete. However, the features of this material must be previously evaluated.